Optimization, Characterisation and Evaluation of Biochar Obtained from Biomass of Invasive Weed Crotalaria burhia - Loveena Gaur and Poonam Poonia (Nature Environment and Pollution Technology)
Invasive weed plants are unwanted and hazardous waste biomass; and have extraordinary potential to serve as raw materials for biochar production. To evaluate the potentiality of invasive weed for bioenergy production in the form of biochar, Crotolaria burhia was investigated. The response surface modeling and optimization of the biochar parameters were conducted using the experimental design expert 13.0. The optimum value of the desirability function was obtained at a pyrolysis temperature of 450°C and a particle size of 50-100 mm. The model represents a p-value less than 0.0500 and a high F value, which denotes its reliable and accurate prediction of experimental data. A strong correlation was observed between actual and predicted values for biochar composites fixed carbon, carbon, surface area, pore size, and pore volume. In the present study, C. burhia biochar production was carried out by slow pyrolysis at 450°C under vacuum conditions. Biochar was found to be alkaline, with a 33.23% yield. Proximate analysis of C. burhia revealed 3.35% moisture content, 8.48% volatile matter, 81.24% fixed carbon and 6.94% ash content. The elemental analysis shows major concentrations of carbon, hydrogen, and oxygen as 57.77%, 6.123%, and 27.60%, respectively. Low H/C and O/C molar ratios were quantified as 0.10% and 0.47%, respectively. It possesses a honeycomb structure having mesoporous surface porosity with a surface area of 155.19m²/g and the presence of a remarkable concentration of mineral elements calcium and potassium. Biochar rich in hydroxyl, carboxylic, and alkene functional groups enhances its applicability areas. These findings make C. burhia a potential feedstock for the production of good-quality biochar.